Pengaruh Promosi Kesehatan Terhadap Keberhasilan ASI Eksklusif - Baiq Zulvita Rahayu (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Background: To achieve optimal use of exclusive breastfeeding, it is stated in the Government Regulation of the Republic of Indonesia number 33 of 2012 concerning exclusive breastfeeding that health workers and health service facility providers are obliged to provide information and education on exclusive breastfeeding to mothers and/or family members. of babies who are cared for from the pregnancy check up to the end of the exclusive breastfeeding period. Method: The research carried out was a Narrative Literature Review (NLR). Results: There were 10 selected scientific articles ranging from 2017 to 2023. To increase the success of exclusive breastfeeding, appropriate health promotion strategies are needed, such as creating special Standard Operating Procedures (SOPs) for the promotion of exclusive breastfeeding, the availability of media and educational tools such as posters, leaflets, and providing training for health workers to increase the knowledge of health workers, especially midwives, as close contacts in providing counseling during pregnancy, postpartum and newborns. Conclusion: Health promotion during pregnancy can increase the success of exclusive breastfeeding.